BLOOD TYPE DETECTION AS AN EFFORT TO INCREASE STUDENTS' HEALTH AWARENESS AT SMPN 5 TINGGI MONCONG IN GOWA, SOUTH SULAWESI - Liana, Alin; Herlina, Herlina; Samsi, Andi Nur; Andariana, Andi; Purnamasari, Andi Bida (Jurnal Pengabdian Masyarakat Biologi dan Sains, 2025)
Gaining knowledge of blood type is crucial for individual health, particularly when facing emergencies that require immediate transfusion or medical decisions. However, many adolescents, especially those in rural areas, lack awareness of their own blood types. This community service project aimed to increase blood type literacy and conduct actual blood type screening among students of SMPN 5 Tinggi Moncong in Gowa, South Sulawesi. A total of 26 students participated in a structured program consisting of health education sessions, demonstrations, and hands-on blood type screening using the slide agglutination method with anti-A, anti-B, anti-AB, and anti-Rh reagents. The results showed that blood type A was the most common (42%), followed by types B and AB (23% each), and type O (12%). Post-activity surveys indicated that students experienced increased awareness, reduced anxiety, and greater motivation to encourage family members to know their blood types. The activity not only served as a health awareness tool but also helped introduce practical biological knowledge in a rural educational context. This model can be replicated in other underserved schools to promote early health preparedness and reduce barriers to essential health information. Pengetahuan tentang golongan darah sangat penting bagi kesehatan individu, terutama dalam situasi darurat yang membutuhkan transfusi atau keputusan medis secara cepat. Namun, banyak remaja, khususnya di daerah pedesaan, yang belum mengetahui golongan darah mereka. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan literasi tentang golongan darah serta melakukan pemeriksaan langsung terhadap siswa SMPN 5 Tinggi Moncong di Kabupaten Gowa, Sulawesi Selatan. Sebanyak 26 siswa mengikuti rangkaian kegiatan yang terdiri atas sesi edukasi kesehatan, demonstrasi, dan pemeriksaan golongan darah menggunakan metode slide aglutinasi dengan reagen anti-A, anti-B, anti-AB, dan anti-Rh. Hasil menunjukkan bahwa golongan darah A paling banyak ditemukan (42%), diikuti oleh golongan B dan AB (masing-masing 23%), serta golongan O (12%). Survei pascakegiatan menunjukkan peningkatan kesadaran siswa, penurunan rasa takut, dan motivasi yang lebih besar untuk mendorong anggota keluarga juga mengetahui golongan darah mereka. Kegiatan ini tidak hanya berfungsi sebagai sarana edukasi kesehatan, tetapi juga menjadi media pembelajaran biologi praktis di lingkungan sekolah pedesaan. Model ini dapat direplikasi di sekolah-sekolah lainnya untuk mendorong kesiapsiagaan kesehatan sejak dini dan mengurangi kesenjangan akses terhadap informasi kesehatan dasar.